FractWhale-DSR: Fractional Whale Optimization Based Secure Dynamic Source Routing Algorithm for Mobile Ad-hoc Network - Suma, Putra; Hussain, Mohammed A. (Recent Advances in Computer Science and Communications, 2020)
Background: Nodes in the mobile Ad-hoc network (MANET) have the dynamic nature due to their vast separation distance. The dynamic nature of the MANET nodes changes the routing path established for the communication. The dynamic secured routing (DSR) has gained popularity since they provide the routing path based on the demand provided by the source and destination nodes. Various literature works have discussed the DSR strategy for routing path establishment, but faces challenges since it consumes high energy during the route discovery phase. Objectives: To overcome the challenges in the existing works, a DSR strategy based on the Fractional Whale optimization algorithm (FWOA) is introduced in this work. Methods: The proposed algorithm uses the C 2 TE based selection criteria which depend on the connectivity, congestion, trust, and energy for selecting the suitable nodes for the communication. The proposed FractWhale-DSR algorithm finds the secured routing path in three phases. Results: The parameters, such as throughput, delay, Packet Delivery Ratio (PDR), and the energy define the performance of the proposed model. From the simulation results, the proposed FractWhale- DSR algorithm has an overall better performance with the values of 0.57265, 0.005118, 0.786325, and 75.88636% for throughput, delay, PDR, and energy respectively at the round of 25 for the MANET with 100 nodes. Conclusion: The proposed DSR strategy has the advantage of adaptability and scalability. Also, the router selects the alternate paths, when there is a link failure in the current network.
Keywords: fractional whale optimization algorithm